Molecular Nuclear Medicine The Challenge of Genomics and Proteomics to Clinical Practice - Feinendegen, Ludwig E.; Shreeve, Walton W.; Eckelman, William C.; Bahk, Yong-Whee (Springer Berlin Heidelberg, 2003)
Nuclear Medicine techniques have advanced to such a degree that biochemical transparency of the human body has reached the doorstep of medical application. The book gives background, techniques and examples in an interdisciplinary approach to quantify biochemical reactions in vivo by regional imaging and in vitro analyses. The goal is to assess in vivo biochemical homeostatic circuits under control by genes and protein interactions. It becomes apparent how nuclear medicine can aid clinical researchers and practitioners, human geneticists and pharmacologists in understanding (and affecting) gene-phenotype relationships operating in vivo and thus can help eventually to bring functional genomics and proteomics to clinical medicine.
Keywords: Nuclear Medicine; Imaging / Radiology; Cancer Research; Molecular Medicine; Hematology; Oncology; Nuclear medicine; Radiology, Medical; Medicine; Oncology; Molekulargenetik; Nuklearmedizin; Aufsatzsammlung